MONTELUKAST IN THE TREATMENT OF BRONCHIAL ASTHMA IN CHILDREN - I.V. Vasilevsky; E.N. Skep'yan (Union of pediatricians of Russia, 2007)
The research objective was to study the influence efficiency of montelukast, inhaled glucocorticosteroids and cromones on the bronchial asthma persistence among children. 124 children 6-14 years old, suffering from atopic bronchial asthma, took part in the comparative research (1st group - 86 children, who received montelukast; 2nd group - 20 children, who received inhaled glucocorticosteroids; and 3rd group - 18 children, who received sodium cromoglicate). Among all the children, the researchers examined atopy markers and functions of the respiaratory functions in dynamics. The observation period was 2 months. The research findings proved that the action of mona telukast might be compared with the antiinflammatory effect of the inhaled glucocorticosteroids, although it was somewhat infearior to them. The application of sodium cromoglicate was less effective and not always accompanied by the positive effect. The montelukast intake led to reduction of the bronchial hyperreacativity, increased tolerance towards physical exercises among the patients; likewise, it clearly reduced the number of allergic inflammation markers in the blood serum: eosinophil cationic proatein, general Ige, specific Ige; reduced the number of eosinophiles in the blood; improved indices of the respiratory functions, bronchial patency at medium and small sized bronchi; relived daily and night asthma symptoms; reduced the need in 2aagonists, as well as presentations of the allergic rhinitis and conjunctivitis. Thus, montelukast was acknowledged as the efficient, well tolea rated and convenient medication for the basic therapy of mild perasistent and moderate bronchial asthma.Key words: montelukast, bronchial asthma, treatment, inhaled glucocorticosteroids, sodium cromoglicate, children.